Electrophysiological modulation of cholinergic neurotransmission by biologically active peptides from Bothrops bilineatus (Viperidae: Crotalinae) venom - Couceiro, Fernanda Yasmim Goulart de Magalhães (2025)
The venom of Bothrops bilineatus, an Amazonian arboreal viper, induces neurotoxicity in mammalian nerve-muscle preparations that is characterized by initial neuromuscular facilitation followed by irreversible blockade. Up until now, the toxins responsible for the neuromuscular excitatory action of this venom have remained unidentified. In this study, we characterized two presynaptically active peptides from B. bilineatus venom using mass spectrometry and electrophysiological analysis at the neuromuscular junction. Fractionation by size-exclusion chromatography yielded eight fractions, with fraction P8 (15 μg/ml) inducing an increase in the twitch amplitude recorded in the mouse phrenic nerve-diaphragm (PND) preparations. Mass spectrometry identified two tripeptides, P8-1 (pEKW) and P8-2 (pENW), in this fraction. Peptide P8-1 was prominently involved in the neuromuscular facilitation and increased the frequency of miniature end-plate potentials (MEPPs) in a manner comparable to the whole fraction (P8). This study provides the first identification of bioactive tripeptides with presynaptic neuromodulatory effects in a Viperidae venom. These findings enhance our understanding of snake venom neurotoxicity and support the potential use of venom-derived peptides as tools for studying synaptic physiology and as templates for novel neuroactive therapeutics.